Effect of Ethyl Chloride Spray for Pain Reduction during Amniocentesis: A non – blinded randomized controlled trial - Telapol, Kritakarn; Bumrungphuet, Sommart; Israngura Na Ayudhya, Nathpong (Thai Journal of Obstetrics and Gynaecology, 2018)
Objectives: To evaluate the cryo-analgesic effect of ethyl chloride spray on reducing pain during second-trimester amniocentesis. Materials and Methods: A non-blinded randomized controlled trial was performed to compare the post-procedural pain scores during second-trimester amniocentesis between pregnant women who received and did not receive ethyl chloride spray immediately before amniocentesis needle penetration. Outcome was mean of post-procedural pain score measured by using visual analogue scale (VAS). Results: The study was performed between May and November 2016. One hundred and forty-eight participants were randomly divided into two groups received cryo-analgesia using ethyl chloride spray and did not receive. There were no differences between demographic data and pre-procedural pain scores (anticipated pain) (p = 0.6). Mean post-procedural pain score in the cryo-analgesia group was significantly lower than the control group (p = 0.01). Six participants in cryo-analgesia group had frostbite skin rash (8%) which was self-limiting condition and persists for about one month with no scar. Most participants (98%) willingly accepted to undergo the procedure again if indicated. Conclusion: Ethyl chloride spray may be an alternative method for amniocentesis procedural pain management. Women should be informed about the potential risk of complications. Keywords: Amniocentesis, pain, ethyl chloride spray, visual analogue scale.